Development and validity evidence of an objective structured assessment of technical skills score for minimally invasive linear-stapled, hand-sewn intestinal anastomoses: the A-OSATS score - Schmidt, Mona Wanda; Haney, Caelán Max; Kowalewski, Karl-Friedrich; Bintintan, Vasile; Abu Hilal, Mohammed; Arezzo, Alberto; Bahra, Marcus; Besselink, Marc G.; Biebl, Matthias; Boni, Luigi; Diana, Michele; Egberts, Jan-Hendrik; et al. (Surgical endoscopy and other interventional techniques, 2021)
The aim of this study was to develop a reliable objective structured assessment of technical skills (OSATS) score for linear-stapled, hand-sewn closure of enterotomy intestinal anastomoses (A-OSATS).